2014
DOI: 10.3126/narj.v9i0.11644
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long-term Use of Organic and Inorganic Nutrients on HLB Disease of Wheat under Rice-Wheat Cropping Pattern

Abstract: Helminthosporium leaf blight (HLB) is one of the most destructive diseases of wheat in terai (plain) region of Nepal. This study was conducted to determine the effect of long-term application of various levels of nitrogen (N), phosphorus (P), potassium (K) and organic nutrients on HLB disease of wheat. The experiment was superimposed on long-term fertility experiment conducted in RCB design with three replications under rice-wheat cropping pattern at National wheat research program (NWRP), Bhairahawa, Nepal. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Increased crop resilience due to agronomic interventions such as crop residue management and application of fungicide (mancozeb @ 2.5 gm/lt of water) at the time of disease emergence may have contributed to the minimum disease severity of 18% (Mandya) and 26% (Chikkaballapura). The current study's findings on disease severity are similar to those observed by Bhandari (2010). When compared to healthy plants, the incidence of wheat spot blotch ( B. sorokiniana ) disease is more severe under stress conditions and in weak plants.…”
Section: Discussionsupporting
confidence: 91%
“…Increased crop resilience due to agronomic interventions such as crop residue management and application of fungicide (mancozeb @ 2.5 gm/lt of water) at the time of disease emergence may have contributed to the minimum disease severity of 18% (Mandya) and 26% (Chikkaballapura). The current study's findings on disease severity are similar to those observed by Bhandari (2010). When compared to healthy plants, the incidence of wheat spot blotch ( B. sorokiniana ) disease is more severe under stress conditions and in weak plants.…”
Section: Discussionsupporting
confidence: 91%
“…The losses due to the disease in Nepal ranged from 23 -40 % depending on genotypes and other environmental factors (Shrestha et al, 1998;Bhandari and Tripathi, 2005;Sharma and Duveiller, 2006). Resistant genotypes, foliar spray of fungicides and nutrients management are effective against the disease (Duveiller, 2002;Regmi et al, 2002;Bhandari, 2010). Application of Triazoles fungicides can suppress the disease effectively (Bhandari and Gharti, 2002;De-Viedma and Kohli, 1997).…”
mentioning
confidence: 99%